Comparative outcome analysis of internal screw fixation and Kirschner wire fixation in the treatment of scaphoid nonunion - Engel, Holger; Xiong, Lingyun; Heffinger, Christian; Kneser, Ulrich; Hirche, Christoph (Journal of plastic, reconstructive & aesthetic surgery, 2020)
In cases with difficult scaphoid screw placement due to small, fragile bone fragments, or transplants and insufficient space, the internal Kirschner wire fixation is a fallback option; however, controversy remains regarding its stability, safety, and outcome. Between 2001 and 2011, 95 patients were treated in our center (n=80 with cannulated compression screws and n=15 with Kirschner wires), and retrospectively analyzed. The outcome measurements included the analysis of patient data, union rate and analysis of functional measures, and quality of life. Bony reconstructions were performed with Vascularized Bone Grafts (VBG) based on the 1,2-Intercompartmental Supraretinacular Artery (ICSRA) , Medial Femoral Condyle (MFC)-VBG, cancellous bone, and iliac crest grafts. Bony healing and functional outcome showed no significant differences between Kirschner wire fixation and cannulated compression screws, although significantly more 1,2-ICSRA-VBG were treated with Kirschner wires. Although predominantly used as an intraoperative fallback option, our data demonstrate that Kirschner wire internal fixation can be safe and reliable, with comparable bony union rates and excellent functional outcomes.
Gesehen am 08.10.2020